Effect of Lutein and Antioxidant Supplementation on VEGF Expression, MMP-2 Activity, and Ultrastructural Alterations in Apolipoprotein E-Deficient Mouse. (30th April 2013) - Fernández-Robredo, Patricia; Sádaba, Luis M.; Salinas-Alamán, Angel; Recalde, Sergio; Rodríguez, José A.; García-Layana, Alfredo
Abstract : Oxidative stress is involved in the pathogenesis of several diseases such as atherosclerosis and age-related macular degeneration (AMD). ApoE-deficient mice (apoE −/− ) are a well-established model of genetic hypercholesterolemia and develop retinal alterations similar to those found in humans with AMD. Thus supplementation with lutein or multivitamin plus lutein and glutathione complex (MV) could prevent the onset of these alterations. ApoE −/− mice (n = 40, 3 months old) were treated daily for 3 months with lutein (AE-LUT) or MV (two doses): AE-MV15 (15 mg/kg/day) and AE-MV50 (50 mg/kg/day) and were compared to controls with vehicle (AE-C). Wild-type mice (n = 10 ) were also used as control (WT-C). ApoE −/− mice showed higher retinal lipid peroxidation and increased VEGF expression and MMP-2 activity, associated with ultrastructural alterations such as basal laminar deposits, vacuoles, and an increase in Bruch's membrane thickness. While lutein alone partially prevented the alterations observed in apoE −/− mice, MV treatment substantially reduced VEGF levels and MMP-2 activity and ameliorated the retinal morphological alterations. These results suggest that oxidative stress in addition to an increased expression and activity of proangiogenic factors could participate in the onset or development of retinal alterations of apoE −/− mice. Moreover, these changes could be prevented by efficient antioxidant treatments.